2014
DOI: 10.1002/hep.26889
|View full text |Cite
|
Sign up to set email alerts
|

Small proline rich protein 2a in benign and malignant liver disease

Abstract: STAT3-driven expression of small proline rich protein 2a (SPRR2a), which acts as an src homology 3 (SH3) domain ligand, induces biliary epithelial cell (BEC) epithelialmesenchymal transition (EMT), which, in turn, promotes wound healing. SPRR2a also quenches free radicals and protects against oxidative stress and DNA damage in nonneoplastic BEC. Sprr2a-induced EMT also increases local invasiveness of cholangiocarcinomas (CC), but prevents metastases. Understanding SPRR2a regulation of EMT has potential for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
(84 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, they showed that mesenchymal markers such as ZEB1 and vimentin were more abundantly expressed, whereas an epithelial marker, E-cadherin, was much less abundantly expressed in hepatic stem cell-like ICC cases as compared with mature hepatocyte-like ICC cases in mRNA levels. Another finding reported that ZEB1 correlates with the differentiation status of ICC cells, furthermore, Mizuguchi showed that small proline-rich protein 2a complexes with ZEB1 repress mirR-200c/141 transcription in ICC cells, thereby inducing EMT 15. These results were support of our finding of the clinical significance of ZEB1 in ICC, and ZEB1 is recognised as a key molecule of the EMT in ICC.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, they showed that mesenchymal markers such as ZEB1 and vimentin were more abundantly expressed, whereas an epithelial marker, E-cadherin, was much less abundantly expressed in hepatic stem cell-like ICC cases as compared with mature hepatocyte-like ICC cases in mRNA levels. Another finding reported that ZEB1 correlates with the differentiation status of ICC cells, furthermore, Mizuguchi showed that small proline-rich protein 2a complexes with ZEB1 repress mirR-200c/141 transcription in ICC cells, thereby inducing EMT 15. These results were support of our finding of the clinical significance of ZEB1 in ICC, and ZEB1 is recognised as a key molecule of the EMT in ICC.…”
Section: Discussionsupporting
confidence: 89%
“…Small proline rich protein 2a (SPRR2a) overexpression in CCA cells induced EMT, which in turn promotes invasiveness [59,120]. Further experiments showed that SPRR2A acts as a transcriptional corepressor with ZEB1 to repress miR-200c/141 transcription in CCA cells in order to maintain a mesenchymal phenotype [59].…”
Section: Additional Regulatory Factorsmentioning
confidence: 99%
“…Further experiments showed that SPRR2A acts as a transcriptional corepressor with ZEB1 to repress miR-200c/141 transcription in CCA cells in order to maintain a mesenchymal phenotype [59].…”
Section: Additional Regulatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a kind of important but delicate cells, cholangiocytes are also sensitive to oxidative stress and involved in the process of cholangiopathies [9,10]. Although an increasing number of studies have investigated intracellular mechanisms and therapeutic targets to prevent H/R-induced hepatocyte injury [3,11,12], only a few have focus on H/R-induced cholangiocyte injury.…”
Section: Introductionmentioning
confidence: 99%